Feasts of Indifference: Racialization, Affect, and Necropolitics in 1X War Games - Mahshid Mayar (European Journal of American Studies)
Graphically and narratively simple war games such as the critically acclaimed, counter-narrative September 12th (2003) and the heavily criticized and deleted Muslim Massacre (2008)—titles that I refer to as 1X war games—trade in the overall logic of necropolitics. I refer to these games as 1X because, in encountering America’s enemies, they promote only the last of the 4X game-verbs, that is, “eXterminate.” In other words, instead of planning how to best train for, track down, encounter, and ultimately fight against this enemy, the choice that these controversial, post-9/11games offer is to simply eliminate the already out-at-large, under-armed, erratic Muslim enemy in a drone-like, distanced, and lackluster manner. As I suggest in this essay, 1X games promote unappealing and non-immersive, yet overtly political projects of death. Adopting Achille Mbembe’s notion of necroplitics in the ludic, mechropolitical sense proposed by Amanda Phillips, I focus on these games’ opposing, yet usefully comparable, approaches to enmification through racialization through entertainment—a two-step project of death that, nodding to Sharon Patricia Holland, I understand as affective, yet heedless feasts of indifference.